Cultural Hegemony in J. K. Rowling’s Harry Potter Series - Shalih Dzakiyyah Farda (English Department, Faculty of Humanities, Andalas University, 2018)
This article discusses the issue of politics and hegemony in Harry Potter, a fantasy series by British author J. K. Rowling. The work is apparently coded with class systems and hierarchy in its society, and how it can be seen as a reflection of real-life society. It explores how the ruling group tries to keep the power only on the hands of the few by inserting their views and ideologies to their people, and thus resulting into a certain status quo that the ruling group finds desirable. The seven novels of Harry Potter are analysed through Marxist perspective using Antonio Gramsci’s theory of Cultural Hegemony, in which the people in power impose and spread their ideas to those below them as a way to control them. It is concluded that the series also involves criticisms on class domination, corruption on power, and rebellion.